Perceptions of entrepreneurship with the support of technological tools: a descriptive approach in times of COVID-19 (National Administration Journal, 2021)
This article examines entrepreneurship in the face of the coronavirus pandemic. Some research was established, whose objective was to discover the perceptions of undertaking in times of COVID-19, with the help of technological tools for the orientation of ongoing businesses and value proposals adaptable to the current market situation. The methodology is based on a quantitative approach, with a descriptive depth, with a non-experimental study, using the questionnaire as a data collection tool and a bibliographic review based on a sample of 220 people. The results indicate that in the midst of the pandemic there is a lot of uncertainty to undertake, and in the face of the threatening situation, there is a growing need for the support of technological tools promoted by the impulse of elements such as: motivation, leadership, the search for training and financial advice.
Keywords: Entrepreneurship; economic crisis; ict; covid-19; challenges; policies to promote entrepreneurship